Analysis of Data Obtained From Chromosomal StudiesPerformed During the Period from 2000-2007A Retrospective Study - Saleh, Eman M.; mohymen, nidhal abdul (Journal of the Faculty of Medicine Baghdad, 2008)
Background:generally genetic disorders are a leading cause of spontaneous abortion,